Psychiatric comorbidities and smoking behavior in chronic obstructive pulmonary disease: A case–control study from a north Indian tertiary Center - Rohit Pathak; Abhishek Pathak; Manish Singh (Asian Journal of Medical Sciences, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is increasingly recognized as a condition with multisystem involvement, including psychiatric comorbidities. Tobacco smoking, a primary etiological factor for COPD, may also predispose individuals to psychological distress.